2014
DOI: 10.1007/s12031-014-0445-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Second Ecto-5′-Nucleotidase Variant Besides the Usual Protein in Symptomatic Phase of Experimental Autoimmune Encephalomyelitis

Abstract: Ecto-5'-nucleotidase/cluster of differentiation 73 (CD73) (eN) is a 70-kDa glycoprotein expressed in several different mammalian tissues and cell types. It is the rate-limiting enzyme of the purine catabolic pathway, which catalyzes the hydrolysis of AMP to produce adenosine with known anti-inflammatory and immunosuppressive actions. There is strong evidence for lymphocyte and endothelial cell eN having a role in experimental autoimmune encephalomyelitis (EAE), but the role of eN in cell types within the centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 55 publications
2
36
0
Order By: Relevance
“…Prior studies demonstrated that experimentally induced conditions of brain injury in vivo were associated with the increased and selective expression of ecto-nucleotidases (Braun et al 1998;Nedeljkovic et al 2006Nedeljkovic et al , 2008Lavrnja et al 2009Lavrnja et al , 2015Gandelman et al 2010;Bjelobaba et al 2011), while eN-deficient animals (Mills et al 2008) were resistant to experimentally induced neuroinflammation. These findings may be of pathophysiological importance, as they implicate the enzymes in the process of modulation of neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies demonstrated that experimentally induced conditions of brain injury in vivo were associated with the increased and selective expression of ecto-nucleotidases (Braun et al 1998;Nedeljkovic et al 2006Nedeljkovic et al , 2008Lavrnja et al 2009Lavrnja et al , 2015Gandelman et al 2010;Bjelobaba et al 2011), while eN-deficient animals (Mills et al 2008) were resistant to experimentally induced neuroinflammation. These findings may be of pathophysiological importance, as they implicate the enzymes in the process of modulation of neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, altered expression of ecto-nucleotidases has been associated with numerous pathologies in different tissues and cell types (Antonioli et al 2013). Upregulation of microglial NTPDase1 and astroglial ecto-5′-nucleotidase (eN) was found in several experimental models of human dysfunctions (Braun et al 1998;Nedeljkovic et al 2006Nedeljkovic et al , 2008Lavrnja et al 2009Lavrnja et al , 2015Gandelman et al 2010Bjelobaba et al 2011, and together, both enzymes promote hydrolysis of extracellular ATP to adenosine. Studies performed in vitro identified some of the signaling factors that may contribute to the observed induction of the ectonucleotidases during the neuroinflammatory state in vivo (Brisevac et al 2012(Brisevac et al , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it was concluded that astrocytes become reactive even before infiltration of immune cells in the CNS (Eng, D'Amelio, & Smith, ). At the onset of clinical deficits in EAE animals, astrocytes start to proliferate, while elongated fibrous branches border inflammatory infiltrates (Lavrnja et al, ). During the inflammatory phase of the disease, astrocytes undergo massive proliferation and extensive hypertrophy of cell bodies with enlarged intertwining processes, forming the scar border (Lavrnja et al, ).…”
Section: Experimental Autoimmune Encephalomyelitismentioning
confidence: 99%
“…Those events are associated with the demyelination process, together with neurodegeneration, mainly seen in the lumbosacral region of the spinal cord (Lavrnja et al, ; Milicevic et al, ; Papadopoulos, Pham‐Dinh, & Reynolds, ). Around areas of demyelination, reactive astrocytes forming glial scar can be found (Lavrnja et al, ). In addition, there is an accumulation of T cells and neutrophils in cerebrospinal fluid, suggesting that in EAE, choroid plexus is a site of entrance for immune cells (Schmitt et al, ).…”
Section: Selection Of Animals In Eaementioning
confidence: 99%
“…Both P2X7 receptors and the P2Y-like GPR17 receptor were shown to be involved in MS [29,42]. Upregulation of ecto-5'-nucleotidase (CD73) during experimental autoimmune encephalomyelitis, a model of MS, has been reported [43].…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 99%